Release and stability of two tebuconazole nanoformulations in different aquatic media - López-Cabeza, Rocío; Eghbalinejad, Mahleh; Kah, Melanie; Grillo, Renato [UNESP]; Bílková, Zuzana; Kotouček, Jan; Hofman, Jakub (Royal Society of Chemistry, 2024)
Novel formulations for pesticides based on nano-sized carriers loaded with active substances (i.e., nanopesticides) have been developed in recent years to enhance the technical, environmental, and toxicological properties of pesticides. However, more is needed to know about the behavior of nanopesticides in media used for ecotoxicological tests. In this work, the release and stability of two tebuconazole (TBZ) nanoformulations (TBZ loaded on poly-ε-caprolactone [PCL] or on nanolipids [NLC]) were evaluated in Milli-Q water (control) and two media used broadly in ecotoxicological tests: reconstituted water (RCW) and Elendt M7 solution. The results suggested that the release of the TBZ depended mainly on the TBZ concentration in the system with faster release at lower concentration levels. TBZ release was also influenced by the type of nanocarrier. For instance, for RCW and concentration of 50 mg/mL, TBZ release from NLC (plateau % = 44.7 ± 2.6) was higher than from PCL (plateau % = 17.8 ± 2.6). Similar trends were also found for other concentrations and the other medium, M7. The colloidal stability of the nanoformulations declined as the concentration of the stabilizing agents decreased. Our results show that it is essential to consider the factors that could influence both the release and stability of the nanopesticides in ecotoxicological media since these phenomena can affect the exposure of organisms to pesticides and, therefore, the results of ecotoxicological tests.
Liberação e estabilidade de duas nanoformulações de tebuconazol em diferentes meios aquáticos